On Early and Late Modern English Non-native Suffix -oon - Wright, Laura (International Journal of English Studies, 2020)
This paper is about identifying a nuance of social meaning which, I demonstrate, was conveyed in the Early and Late Modern period by the suffix -oon. The history of non-native suffix -oon is presented by means of assembling non-native suffix -oon vocabulary in date order and sorting according to etymology. It turns out that standard non- native -oon words (which are few) tended to stabilise early and be of Romance etymology. A period of enregisterment, c. 1750–1850, is identified by means of scrutiny of non-native -oon usage in sixty novels, leading to the conclusion that four or more non-native -oons in a literary work signalled vulgarity. A link is made between the one-quarter non-European -oons brought to English via colonial trade, and the use of such -oons by non-noble merchants, traders and their customers splashing out on luxury foreign commodities. Thus, it is found that a suffix borrowed from Romance languages in the Middle English period received fresh input during the Early Modern period via non-European borrowings, resulting in sociolinguistic enregisterment in the Late Modern period.